Efficiency-Aware: Maximizing Energy Utilization for Sensor Nodes Using Photovoltaic-Supercapacitor Energy Systems - Zheng Liu; Xinyu Yang; Shusen Yang; Julie McCann (International Journal of Distributed Sensor Networks, 2013)
Recently, photovoltaic-supercapacitor-based energy systems have become more and more popular in the design of energy harvesting wireless sensor networks (EH-WSNs) as an alternative to battery power. Existing research on this area mainly focuses on hardware design and the improvement of the charging efficiency. However, energy is wasted not only by the inefficient charging process, but also the inefficient discharging process and energy leakage. Therefore, to maximize node lifetime and energy utilization, all the previous energy loss should be considered. In this paper, we develop realistic hardware models of the complete photovoltaic-supercapacitor energy systems and propose the efficiency-aware , a systematic duty cycling framework to maximize energy utilization. We formalize the maximization problem as a nonlinear optimization problem and develop two efficient algorithms for its optimal solutions. The performance of our approaches is evaluated via extensive numeric simulations, and the results show that our efficiency-aware framework can, respectively, achieve 60% and 56% more active time (i.e. energy utilization) than the fixed duty cycle scheme and leakage-aware , a state-of-the-art scheme for photovoltaic-supercapacitor energy systems.